2020
DOI: 10.21876/rcshci.v10i2.868
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência da constipação intestinal em acadêmicos de medicina de uma instituição particular do estado de Tocantins, Brasil

Abstract: Objetivos: Analisar a prevalência e características da constipação intestinal (CI) em acadêmicos de medicina de uma instituição particular do Estado do Tocantins, Brasil. Métodos: Estudo transversal e quantitativo, com aplicação de questionário a acadêmicos de medicina do 1º, 3º e 6º período. Foi realizada a coleta de dados gerais e específicos, de agosto a setembro de 2018, para a caracterização da CI, seguido de estatística descritiva. Resultados: A maioria dos 142 entrevistados era do 1º semestre do curso (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…15,[20][21][22][23][24] Gallas et al, 25 in their pilot study involving medical students from Tunisia, revealed a CIC prevalence of 11.6%. De Aquino et al, 26 assessing CIC in medical students from a higher educational institution from the state of Tocantins, Brazil, showed a selfdeclared prevalence of CIC of 15.5 and 26.7% according to the ROME III criteria. Similarly, Trisóglio et al 18 indicated that 35% of medical students from an institution in northwestern São Paulo state presented constipation, from which the great majority were females (55%).…”
Section: Cic Incidence In College Studentsmentioning
confidence: 99%
“…15,[20][21][22][23][24] Gallas et al, 25 in their pilot study involving medical students from Tunisia, revealed a CIC prevalence of 11.6%. De Aquino et al, 26 assessing CIC in medical students from a higher educational institution from the state of Tocantins, Brazil, showed a selfdeclared prevalence of CIC of 15.5 and 26.7% according to the ROME III criteria. Similarly, Trisóglio et al 18 indicated that 35% of medical students from an institution in northwestern São Paulo state presented constipation, from which the great majority were females (55%).…”
Section: Cic Incidence In College Studentsmentioning
confidence: 99%